Six new species of Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) with redescription of additional species and new distributional records - Duan, Yani; Zhang, Yating; Dietrich, Christopher H. (Zootaxa, 2019)
Six new species of Stenometopiini are described: Stirellus paracatalinus sp. nov. from Mexico, Stirellus lesioensis sp. nov. from Republic of Congo, Stirellus paralesioensis sp. nov. from South Africa, Stirellus kitwensis sp. nov. from Zambia, Stirellus madagascarensis sp. nov. from Madagascar, and Stirellus petfordensis sp. nov. from Australia. Ten species are redescribed: Kinonia elongata Ball, Stirellus catalinus (Beamer & Tuthill), Stirellus labiatus (Gillette), Stirellus mexicanus (Osborn & Ball), Stirellus picinus (Berg), Stirellus laetus (Melichar), Stirellus multipunctatus Duan, Webb & Zhang, Stirellus neospeciosus Duan, Webb & Zhang, Stirellus rubrolineatus (Distant), and Stirellus sagittarius (Naudé). Kinonia elongata Ball, S. catalinus (Beamer & Tuthill) and S. labiatus (Gillette), all described from the Southwestern USA, are recorded from Mexico for the first time. Stirellus picinus (Berg) is recorded from the Virgin Islands (Guana Island) for the first time. Stirellus laetus (Melichar), S. multipunctatus Duan, Webb & Zhang, S. neospeciosus Duan, Webb & Zhang, and S. rubrolineatus (Distant) are recorded from Thailand for the first time.